Factors and strategies for increasing the income of MSME assistance recipients in Kerinci Regency in the tourism sector in Kerinci Regency - Dermawati, Dermawati; Tan, Syamsurijal; Nurhayani, Nurhayani; Nasrullah, M (The Asian Journal of Professional & Business Studies, 2025)
This study aims to analyze the influence of business location, education, capital, and labor on the income of MSME aid recipients in Kerinci Regency and to analyze strategies for increasing the income of MSME aid recipients in the tourism environment of Kerinci Regency. The analytical tools used in this research are multiple linear regression and SWOT analysis. The results of the study indicate that partially, education, capital, and labor have a significant effect on the income of MSME aid recipients in Kerinci Regency. On the other hand, location does not significantly affect the income of UMKM (Micro, Small, and Medium Enterprises) assistance recipients in Kerinci Regency. Based on the SWOT analysis results, the strategy used to increase the income of UMKM assistance recipients in Kerinci Regency is positioned in quadrant IV, which is the recommendation for a defensive strategy. This means that UMKM assistance recipients in the tourism sector of Kerinci Regency face considerable external threats, while their internal strengths are relatively weak. In this situation, the appropriate strategy is a defensive strategy, which focuses on measures to sustain business operations and gradually improve competitiveness.